Clinicopathologic Characterization of Post–Renal Transplantation BK Polyomavirus-Associated Urothelial CarcinomaSingle Institutional Experience. Issue 3 (19th October 2019) - Chu, Ying-Hsia; Zhong, Weixiong; Rehrauer, William; Pavelec, Derek M; Ong, Irene M; Arjang, Djamali; Patel, Sanjay S; Hu, Rong
Abstract: Objectives: To review rare cases of BK polyomavirus (BKPyV) associated urologic carcinomas in kidney transplant recipients at one institution and in the literature. Methods: We describe the clinicopathologic features of BKPyV-associated urologic carcinomas in a single-institution cohort. Results: Among 4, 772 kidney recipients during 1994 to 2014, 26 (0.5%) and 26 (0.5%) developed posttransplantation urothelial carcinomas (UCs) and renal cell carcinomas (RCCs), respectively, as of 2017. Six (27%) UCs but none of the RCCs expressed large T antigen (TAg). TAg-expressing UCs were high grade with p16 and p53 overexpression ( P < .05 compared to TAg-negative UCs). Tumor genome sequencing revealed BKPyV integration and a lack of pathogenic mutations in 50 cancer-relevant genes. Compared to TAg-negative UCs, TAg-expressing UCs more frequently presented at advanced stages (50% T3-T4) with lymph node involvement (50%) and higher UC-specific mortality (50%). Conclusions: Post-renal transplantation BKPyV-associated UCs are aggressive and genetically distinct from most non-BKPyV–related UCs.